Single-gene knockout-coupled omics analysis identifies C9orf85 and CXorf38 as two uncharacterized human proteins associated with ZIP8 malfunction - Tan, Heng Wee; Xu, Yan-Ming; Liang, Zhan-Ling; Cai, Na-Li; Wu, Yu-Yao; Lau, Andy T. Y. (Frontiers in Molecular Biosciences, 2022)
Human transmembrane protein metal cation symporter ZIP8 (SLC39A8) is a member of the solute carrier gene family responsible for intracellular transportation of essential micronutrients, including manganese, selenium, and zinc. Previously, we established a ZIP8-knockout (KO) human cell model using the CRISPR/Cas9 system and explored how the expression of ZIP8 could possibly contribute to a wide range of human diseases. To further assess the biophysiological role of ZIP8, in the current study, we employed isobaric tags for relative and absolute quantitation (iTRAQ) and detected the changes of the proteome in ZIP8-KO cells (proteomic data are available via ProteomeXchange with identifier PXD036680). A total of 286 differentially expressed proteins (206 downregulated and 80 upregulated proteins) were detected in the ZIP8-KO cell model, and subsequent bioinformatics analyses (GO, KEGG, KOG, and PPI) were performed on these proteins. Interestingly, four “uncharacterized” proteins (proteins with unknown biological function) were identified in the differentially expressed proteins: C1orf198, C9orf85, C17orf75, and CXorf38—all of which were under-expressed in the ZIP8-KO cells. Notably, C9orf85 and CXorf38 were amongst the top-10 most downregulated proteins, and their expressions could be selectively induced by essential micronutrients. Furthermore, clinical-based bioinformatic analysis indicated that positive correlations between the gene expressions of ZIP8 and C9orf85 or CXorf38 were observed in multiple cancer types. Overall, this study reveals the proteomic landscape of cells with impaired ZIP8 and uncovers the potential relationships between essential micronutrients and uncharacterized proteins C9orf85 and CXorf38. The differentially expressed proteins identified in ZIP8-KO cells could be the potential targets for diagnosing and/or treating human ZIP8-associated diseases, including but not limited to malnutrition, viral infection, and cancers.